Research Status and Advances in Improvement Techniques for Dispersive Soil - Zhai, Zhanyi; Yuan, Xiaoqing (Journal of Research in Science and Engineering, 2026)
As a special type of clay soil with strong water sensitivity, dispersive soil poses a significant threat to the stability of water conservancy, transportation, and other infrastructure due to its tendency to disintegrate upon wetting and its weak erosion resistance. This paper systematically reviews the discovery history, distribution characteristics, and engineering hazards of dispersive soil worldwide, with a particular focus on summarizing research progress regarding its dispersion mechanisms, identification methods, and improvement techniques. The review indicates that the dispersivity primarily stems from high exchangeable sodium ion content and an alkaline environment, which increase inter-particle repulsive forces. Its identification requires a combination of various laboratory tests and field investigations. Regarding improvement techniques, current research has expanded from traditional methods such as chemical cation exchange (e.g., using aluminum or calcium salts) and solidification with pozzolanic materials (e.g., fly ash, slag), to the use of organic amendments like lignosulfonates, and environmentally friendly biotechnologies such as Microbially/Enzyme Induced Calcium Carbonate Precipitation (MICP/EICP). Future research should focus on developing efficient, low-cost, and ecologically sustainable improvement technologies, while strengthening the long-term stability assessment of these improvements under complex environmental conditions (e.g., freeze-thaw cycles).